2020
DOI: 10.3390/w12020458
|View full text |Cite
|
Sign up to set email alerts
|

Periurban Transformations in the Global South and Their Impact on Water-Based Livelihoods

Abstract: Urban sprawl and population increase are fundamentally transforming periurban areas in the Global South. These areas often suffer from inadequate environmental planning, resulting in water sources being overexploited, degraded, and redistributed. These processes affect water-based livelihoods due to disadvantages in water access and inadequate water governance. On the positive side, these transformation processes are leading to alternative water-based livelihoods. We systematically review and critically commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 93 publications
(173 reference statements)
0
22
0
Order By: Relevance
“…Among them are obvious ones-like farming, animal husbandry, fishing and aquaculture-but also less obvious ones such as floriculture, brick making, pottery, laundry services, car wash services or tanning. Among them periurban agriculture so far received most attention in the literature [3]. For farmers, water is a decisive input factor, that is getting under pressure through periurbanisation [47][48][49][50].…”
Section: Livelihoodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them are obvious ones-like farming, animal husbandry, fishing and aquaculture-but also less obvious ones such as floriculture, brick making, pottery, laundry services, car wash services or tanning. Among them periurban agriculture so far received most attention in the literature [3]. For farmers, water is a decisive input factor, that is getting under pressure through periurbanisation [47][48][49][50].…”
Section: Livelihoodsmentioning
confidence: 99%
“…The effects of this powerful process are not limited to the cities proper, but also affect the periurban spaces surrounding these cities. These periurban interfaces are spaces of flows, shaped by an exchange of matter, people and ideas between urban and rural spaces [3]. They are characterized by high heterogeneity of land uses [4,5], actors with often conflicting interests [6] and inadequate governance structures [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, the focus was on the dynamic and multi-functionality of peri-urban areas and proposed a non-linear perspective on peri-urban development [29]. The study showed that peri-urban areas are very important, since they provide linkages between urban-rural areas connecting two cities across many nations [25].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Furthermore, urban development has brought positive impact in terms of providing a market from newly developed residential areas for agricultural products [6]. In addition, local communities have gained socio-economic benefits by providing services, such as childcare, cleaning services, and providing food services for middle-income dwellers in peri-urban areas [23,25].…”
Section: Background Of the Studymentioning
confidence: 99%